English as a lingua franca: From theory to practice. (January 2020) - Chen, Yuan-shan; Ren, Wei; Lin, Chih-Ying
Abstract : English as a lingua franca (ELF) refers to 'any use of English among speakers of different first languages for whom English is the communicative medium of choice, and often the only option' (Seidlhofer, 2011, p. 7*). ELF research started relatively recently. It was only discussed occasionally in the last century. Landmark changes were the publications of Jenkins (2000*) and Seidlhofer (2001*). These works inspired more research into ELF, as witnessed by a dramatically increased interest in ELF since then, resulting in a large number of journal articles, monographs, edited books (e.g. Mauranen & Ranta, 2009*) and large corpora (e.g. the Vienna-Oxford International Corpus of English, the Corpus of English as a Lingua Franca in Academic Settings, and the Asian Corpus of English). In addition, ELF researchers have launched the annual conference series (International Conference of English as a Lingua Franca), the Journal of English as a Lingua Franca, and the De Gruyter book series Developments in English as a Lingua Franca. These publications move from an initial understanding of ELF as a 'variety' or 'varieties' to a later conceptualisation of ELF as a dynamic, fluid and variable phenomenon. ELF has become a major focus of discussions and activities among both applied linguists and English language teaching professionals (Jenkins, Cogo, & Dewey, 2011).